COMPOUND REFINEMENT RIETVELD SUPERCONDUCTING YBa2Cu3O7 - González, J.C. (2006)
The superconductor YBa2Cu3O7 compound was synthesized by the sol-gel technique. The pattern of X-ray diffraction showed that the ceramic oxide crystallized in an orthorhombic structure. The structure analysis was performed by allowing Rietveld refinement obtain network parameters, the atomic positions, occupancy of atomic sites, identify dollies and spurious secondary compound and the percentage content of the latter